\(x^2-y^2\)
\(=\left(x-y\right)\cdot\left(x+y\right)\)
Với x =177 ; y=833 thay vào BT ta có
\(\left(177-833\right)\cdot\left(177+833\right)\)
\(=-656\cdot1010\)
\(=-662560\)
ti ck nha
\(x^2-y^2=\left(x-y\right)\left(x+y\right)\left(1\right)\)
Thay x=177,y=833 vào (1) ta được:
\(\left(177-833\right)\left(177+833\right)\)
\(=-656.1010\)
\(=-662560\)
Thay x=177; y=833 vào biểu thức, ta có
1772-8332=-662560
x2 - y2
= (x - y) (x + y)
(Áp dụng hằng đẳng thức 3)
Thay x = 177 và y = 833 vào biểu thức, ta có:
(x - y) (x + y)
= (177 - 833) (177 + 833)
= -656 . 1010
= -662560